2020
DOI: 10.1186/s40813-020-00167-x
|View full text |Cite
|
Sign up to set email alerts
|

The provision of toys to pigs can improve the human-animal relationship

Abstract: It is now widely recognised that a positive human-animal relationship is beneficial not only for farm animals’ welfare but also for productivity and the quality of products. A better understanding of animal emotions is an important goal in disciplines ranging from neuroscience to animal welfare science, but few reliable tools exist for measuring these emotions. In this study, whether the provision of toys to solicit play behaviour in pigs is associated with a change in the human-animal relationship and the emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…On the other hand, these observations are consistent with those carried out on many other species of farm, laboratory, and zoo animals, e.g. minks 36 , polar foxes 37 , pigs 38 , rats, and mice 39 , as well as non-human primates 40 . For example, enriching the cage environment by adding toys (gnawing objects) caused a significant changing of minks’ personalities, as estimated by empathic tests of the movement from “fearful” towards “confident”, while such a reaction was not observed in “aggressive” ones 12 .…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, these observations are consistent with those carried out on many other species of farm, laboratory, and zoo animals, e.g. minks 36 , polar foxes 37 , pigs 38 , rats, and mice 39 , as well as non-human primates 40 . For example, enriching the cage environment by adding toys (gnawing objects) caused a significant changing of minks’ personalities, as estimated by empathic tests of the movement from “fearful” towards “confident”, while such a reaction was not observed in “aggressive” ones 12 .…”
Section: Discussionsupporting
confidence: 89%
“…Reduced locomotor play leads to decreased locomotor function and/or physicality in several species [ 5 , 18 , 19 ]. The experience of object play has been associated with differences in cognition [ 20 , 21 ], and social play experience often has effects on social competence [ 22 24 ]. As useful as the traditional classification of play is, it still overlooks one crucial fact: the observed developmental effects of play are caused by play aspects that may overlap among play types.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that pigs are sensitive to the emotional states of group members, and pigs not directly stimulated can experience emotional states induced by exposure to the emotional responses of their peers which have undergone painful experiences [21]. Following exposure to negative stimuli and restraint treatments, both of the treated pigs and their untreated companions show negative emotional states, despite the companions not experiencing the treatment directly [21][22][23]. Emotional contagion among domestic animals could significantly affect herds' welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Rewards and punishments are central to the elicitation of all emotional states; they determine the valence of emotions [24]. Both food rewards (such as syrup, apples, raisins, and chocolate) and punishment stimuli (including restraints, sudden noises, and thermal stimuli) are effective in inducing emotional states that persist after the stimulus [9,22]. Evidence of emotional contagion needs observers and demonstrators to have the same emotional valence, which provides ideas for this experimental design.…”
Section: Introductionmentioning
confidence: 99%